Active surveillance of patients who have melanoma with a positive sentinel node in an era of effective adjuvant therapy: Early lessons learned … and still learning. Issue 13 (7th April 2021) - Gershenwald, Jeffrey E.
Abstract : The analysis by Broman and colleagues in this issue contributes to a still rapidly developing evidence base of patients with melanoma and a positive sentinel node who are followed with active surveillance. It reveals substantial adoption of randomized clinical trial findings that support active surveillance for these patients and, with limited follow‐up, suggests that loss of regional basin control is a very uncommon event in this era of effective adjuvant therapy.